2018
DOI: 10.14742/ajet.3747
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based epistemic beliefs, engagement in online activities, and intention for constructivist ICT integration among pre-service teachers

Abstract: This study investigated pre-service teachers' epistemic beliefs about the Internet using the Inventory of Internet-Based Epistemic Beliefs (IBEB). Also examined were their belief profiles to delineate the effect of IBEB on pre-service teachers' engagement in online reading activities and intention for ICT integration for constructivist learning activities. Participants were 474 teacher education students in Taiwan. Results revealed the four hypothesised constructsstructure, uncertainty, source, and justificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…Students' Internet epistemic beliefs were assessed using 16 items developed by the Author (2018b). Justification for knowing on the internet (Justification) measured whether a person justified his or her knowledge claims on the Internet by referring to multiple sources, personal experiences, or experts and authority.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Students' Internet epistemic beliefs were assessed using 16 items developed by the Author (2018b). Justification for knowing on the internet (Justification) measured whether a person justified his or her knowledge claims on the Internet by referring to multiple sources, personal experiences, or experts and authority.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding gender differences in online search and Internet epistemic beliefs, previous research showed that males scored higher than females in the behavioural and procedural domain of information search, but no mean differences were observed in the metacognitive domain of information search (Tsai, 2009) and all subscales of Internet epistemic beliefs (Lee, 2018b). Notably, in most OMDRC studies, gender differences were not found or discussed (e.g.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations